A lacustrine fan- delta system in the Pliocene deposits of the Guadix Basin (Betic Cordilleras, South Spain) - Fernández Turiel, J.L.; Viseras, C.; Bluck, B.J. (Cuadernos de Geología Ibérica, 1991)
Sin resumen